Efektivitas Media Pembelajaran Berbasis Website Wordwall terhadap Hasil Belajar Siswa Kelas V pada Mata Pelajaran IPAS Materi Ekosistem yang Seimbang di SDN Batuplat 1 - Koro, Maxsel; Kota, Martha Khristin; Banu, Anselmus; Katu, Eka Putra Novrianto (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
This research aims to determine the effectiveness of the Wordwall website-based learning media on the learning outcomes of class V students in science and science subjects on balanced ecosystems at SDN Batuplat 1. This type of research is quantitative research using a quasi-experimental research design. The form of quasi-experimental design used is a Nonequivalent control group design. This research was located at SDN Batuplat 1 Kupang City. The subjects of this research were 60 class V students who were divided into 2 study groups or 2 classes, namely the experimental class and the control class. Data collection in this research was carried out using observation techniques and comprehension tests (pretest-posttest). The results of research conducted by researchers show that there is an influence of Wordwal website-based learning media on learning outcomes. This is proven by the t-test (independent sample t-test) and obtained a sig (2-tailed) value of 0.00 < 0.05, which means Ho is rejected and Ha is accepted. Then this wordwall website-based learning media is also quite effective in improving student learning outcomes. This was proven by the N-Gain Score test and obtained an average N-Gain score for the experimental class of 65.32 or 65% which was included in the quite effective category with a minimum N-Gain score of 30% and a maximum of 100%. So it can be concluded that the use of wordwall website-based learning media is quite effective in improving the learning outcomes of class V students in science and science subjects with balanced ecosystem material at SDN Batuplat 1.